13. MAISONNEUVE FRACTURE TREATMENT: TWO CASES REPORT (Vietnam Journal of Community Medicine, 2024)
Objective: This article aims to report 2 case of Maisonneuve fracture. The primary goals include contributing to scientific data, as well as sharing insights into the diagnostic and treatment processes.Case report:Case 1: 28 year -old male patient in our hospital with the diagnosis of Maisonneuve fracture of the left ankle with the fibular fracture in middle third. He suffered the surgery for fixation of the fibular, deltoid ligament suture. A year follow up, left ankle function was similar to the right one and he can return to sport.Case 2: 44 year -old female patient in our hospital with the diagnosis of Maisonneuve fracture of the left ankle with the fibular fracture in proximal third. She suffered the surgery for reduction and fixation of the syndesmotic, deltoid ligament suture, but we detect a neglected posterior malleolus fracture which not fixtion. A year follow up, she can walk and the movement of the ankle was normal, but she still had mild pain in the posterior of the ankle. AOFAS score was 90.Discussion: The exactly reduction of the fibular and sydesmosis bring the optimal function of the ankle in fisrt case. In the second one, although the ankle function was recovered for walking and normal daily activitie, the pain in posterior of the ankle indicate the important role in fixation of posterior malleolus in Maisonneuve fractureConclusion: Exactly diagnosis and the strategy are very important for the recovery of the ankle
Keywords: Ankle fracture; Maisonneuve fracture; case report